Territoires occidentaux et du nord de la Pologne : problèmes maritimes - Iwasiewicz, Zbigniew (Warszawa : Wydawnictwo Zachodnie, 1960)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: visserij; zeevaart; Polen